Hubungan Asupan Gizi Dengan Perkembangan Kognitif Anak Pada Kelompok A Di Tk Pertiwi 2 Blimbing Sambirejo Sragen Tahun Ajaran 2016/2017 - Dwi Mulatsih, Sinto; , Drs. Haryono Yuwono,S.E., M.Pd (2017)
The purpose of this research is to know the correlation between nutrition koward and student's cognitive development in group A of TK Pertiwi 2 Blimbing Sambirejo Sragen Academic Year of 2016/2017. This research was located in TK Pertiwi 2 Blimbing sambirejo Sragen it was correlation describtive research. The population of this research was 31 student's and the sample of the research were all the student in A group. This research used sampling random technique random. Data were taken by spreading questionare. While the analiysis data used the correlative analysis techique product moment using the SPSS aplication for Windows 17.00. Based on the research, it could be concluded that there was a positive correlation between nutrition and student's cognitive development. The score was that rarithmetic > rtable with the significant degree is 1% and 5% with the score (0,536 > 0,456) and (0,536 > 0,355). It was true that Ho was rejected and Ha was accepted. It means that there is the correlation between nutrition and student's cognitive development in group A at TK Pertiwi 2 Blimbing Sambirejo Sragen in academic year of 2016/2017 Keywords : Nutritions, Child's Cognitive Development